Cognitive Functioning of Glucocerebrosidase (GBA) Non-manifesting Carriers - Moran, Eileen E.; Bressman, Susan B.; Ortega, Roberto A.; Raymond, Deborah; Nichols, William C.; Palmese, Christina A.; Elango, Sonya; Swan, Matthew; Shanker, Vicki; Perera, Imali; Wang, Cuiling; Zimmerman, Molly E.; et al. (Frontiers in Neurology, 2021)
Mutations and variants in the glucocerebrosidase (GBA) gene are among the most common genetic risk factors for the development of Parkinson's disease (PD). Yet, penetrance is markedly reduced, and less is known about the burden of carrying a single mutation among those without diagnosed PD. Motor, cognitive, psychiatric, and olfactory functioning were assessed in 30 heterozygous GBA mutation carriers without PD (the majority of whom had mild GBA mutations) and 49 non-carriers without PD. Study focus was on domains affected in GBA mutation carriers with PD, as well as those previously shown to be abnormal in GBA mutation carriers without PD. GBA mutation carriers showed poorer performance on the Stroop interference measure of executive functioning when controlling for age. There were no group differences in verbal memory, Montreal Cognitive Assessment (MoCA), overall motor score, or presence of REM sleep behavior disorder or depression. Although total olfaction scores did not differ, GBA mutation carriers with hyposmia had lower global cognition scores than those without hyposmia. As anticipated by the low penetrance of GBA mutations, these findings suggest that pre-manifest non-motor or motor features of PD may not present in most GBA mutation carriers. However, there is support that there may be a subtle difference in executive functioning among some non-manifesting heterozygous GBA mutation carriers, and, combined with olfaction, this may warrant additional scrutiny as a potential biomarker for pre-manifest and pre-clinical GBA related PD.